2001
DOI: 10.1097/00000539-200104000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Volume Variation as a Predictor of Fluid Responsiveness in Patients Undergoing Brain Surgery

Abstract: Stroke volume variation may be used as a continuous preload variable and in combination with the continuously measured cardiac output, defining on-line the most important characteristics of cardiac function, allowing for optimal fluid management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(187 citation statements)
references
References 22 publications
8
168
0
11
Order By: Relevance
“…A more accurate method for preload assessment is based on the heartlung interactions and the measurement of PPV and SVV by arterial waveform analysis in mechanically ventilated patients. Many studies have demonstrated that PPV and SVV are highly sensitive in predicting fluid responsiveness in mechanically ventilated patients undergoing cardiac surgery, neurosurgical procedures, and live transplantation (7)(8)(9). However, some procedures utilize the insufflation of carbon dioxide, such as for minimal laparoscopic manipulations, which induce IAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more accurate method for preload assessment is based on the heartlung interactions and the measurement of PPV and SVV by arterial waveform analysis in mechanically ventilated patients. Many studies have demonstrated that PPV and SVV are highly sensitive in predicting fluid responsiveness in mechanically ventilated patients undergoing cardiac surgery, neurosurgical procedures, and live transplantation (7)(8)(9). However, some procedures utilize the insufflation of carbon dioxide, such as for minimal laparoscopic manipulations, which induce IAH.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently used static preload variables such as central venous pressure (CVP) or pulmonary capillary wedge pressure often fail to provide reliable information on cardiac preload and are not capable of predicting a cardiac response to fluid therapy (5,6). As an alternative to these static variables, stroke volume variation (SVV) and pulse pressure variation (PPV) have been shown to be sensitive predictors of fluid responsiveness in mechanically ventilated patients undergoing cardiac surgery, neurosurgical procedures, and live transplantation (7)(8)(9). Left ventricle preload is highly susceptible to changes in the intrathoracic pressure induced by mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Filling pressures like central venous pressure (CVP) and pulmonary capillary wedge pressure (PCWP) are normally used as parameters of right and left heart preload. But these static indicators have been shown to be poor predictors of fluid responsiveness (2).…”
Section: Introductionmentioning
confidence: 99%
“…The threshold to divide SVV values into normal and high states was set at 10% [6,[15][16][17]. The value of SVV was always ≤ 10% in the 10 measurements each made in 20 patients, while the corresponding value was always >10% in 12 patients.…”
Section: Resultsmentioning
confidence: 99%